Feeding Preference and Development of Sitophilus oryzae L. on Organic and Inorganic Rice Cultivation - Ludji Pantja Astuti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
This study examined the preferences and development of Sitophilus oryzae on different organic and inorganic rice varieties by free-choice and no-choice tests. Feeding preference was assessed by the male and female adult present and the percentage of weight loss. The development was assessed by the numbers of eggs, larvae, pupae, and adults, the period of eggs, larvae, and pupae, the total development time, larval growth index, growth index, and biotic potential. The free-choice test showed that the number of male and female present and the percentage of weight loss were higher on inorganic rice than on organic rice of either the Shinta Nur or IR-64 variety. The no-choice test showed that the numbers of eggs, larvae, pupae, and adults were higher on inorganic rice than on both varieties of organic rice. The period of eggs, larvae, and pupae and the total development time were shorter on inorganic rice than on organic rice. The larval growth index, growth index, and biotic potential were higher on inorganic rice than on organic varieties. Organic rice had high levels of phenolic, amylose, and carbohydrates, but smaller seed size and lower protein levels and ash was preferred less compared with inorganic rice of both varieties.